A convenient synthesis of CHF2O-containing pyrrolidines and related compounds — Perspective building blocks for drug discovery - Levchenko, Kostiantyn; Virstiuk, Ivan; Menshykova, Daria; Pokhodylo, Nazariy (SynOpen)
Fluorine-containing organic molecules, including CHF2O-derivatives, are among the most sought-after in medicinal chemistry. In the current work, a mini-library of 21 compounds with a CHF2O-motif incorporated with azetidine, pyrrolidine (proline), piperidine, 2-azabicyclo[2.2.1]heptane, and 8-azabicyclo[3.2.1]octane cores were synthesized. A multigram scale (10 to 30 g) procedure for synthesizing title compounds from commercially available amino alcohols was studied.